Problems and sufferings of the flood-affected people in Malaysia:A study of three villages in Kelantan - Karim, A.H.M Zehadul; Md. Noon, Hazizan; Mohamad Diah, Nurazzura; Tajuddin, Nor Azlin; Mustari, Sohela; Sarker, Md. Shahidul Islam; Mazumder, Sumon Kumer (Serials Publications, Pvt. Ltd., 2016)
In December 2014, the north-eastern monsoon flood of Malaysia had hit 11 states in the country, displacing thousands of people and simultaneously damaging huge amounts of properties rendering them in an extremely vulnerable situation. This research is an attempt to explore the socio-economic vulnerabilities of those affected by floods in Kelantan as the hardest hit victims of the calamity. The research seeks to identify the socio-structural vulnerabilities of the effected villagers which are visible even as they continue to engage in daily living and other works during and after the floods. To this end, three villages in Kelantan,named Kampung Laloh, Kampung Manjur, and Kampung Manik Urai Lama, were purposively chosen. Based on participant observations and informal and in-depth interviews, it was found that all the villagers during the flood had suffered tremendously from a lack of suitable shelter which caused them to relocate to higher ground offered by nearby higher lands and hills. Based on the discussions remedial suggestions have been made.